When religion meets academia: Millennial Christians becoming cultural Others on a minority-serving campus in the United States. Issue 4 (2nd October 2019) - Chen, Yea-Wen; Chalko, Kelsey; Bonilla, Michael
ABSTRACT: Given that religion is an understudied yet important topic, this exploratory research investigates how millennial Christians negotiate their intersecting cultural identities on college campuses. Specifically, this research took place on a Hispanic-serving, four-year public university in the Southwestern United States. The research team analyzed interview transcripts with student leaders and members of religious organizations. Following analytical steps of thematic analysis, we interrogated three themes: becoming Christian Others on a "liberal" college campus; avowing and ascribed as raced/sexualized/immigrant Christian "outsiders within;" and negotiating contradictions in avowing a faithful college life. The authors conclude by discussing implications for inter-belief communication.